Lasing from chiral doped nematic liquid crystal droplets generated in a microfluidic device. (24th May 2017) - Lucchetta, D. E.; Simoni, F.; Hernandez, R. J.; Mazzulla, A.; Cipparrone, G.
ABSTRACT: Microfluidics generated liquid crystal (LC) droplets are currently used as microresonators in optofluidics applications due to their small size, narrow droplets diameter distributions, high Q-factor and tunability properties. In this work we report a short review regarding lasing from cholesteric liquid crystals (CLCs) confined in spherical microdroplets generated in a thermally stabilized environment by using a microfluidic technique. The photonic bandgaps (PBGs) have been theoretically calculated and experimentally measured as a function of temperature. A wide tuning effect of hundreds of nanometers has been experimentally observed for the main PBG and reported for two different concentrations of the chiral dopant used to give chirality to the nematic LC. A single-droplet lasing effect has been reported and optimized by using a stop flow technique and the dynamic of the reorientation inside the droplets observed under a polarized optical microscope integrated into the experimental setup.